2011
DOI: 10.3171/2010.11.peds10281
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic fenestration of a cerebellopontine angle arachnoid cyst resulting in complete recovery from sensorineural hearing loss and facial nerve palsy

Abstract: Cerebellopontine angle arachnoid cysts are usually asymptomatic, but are frequently found incidentally because of increased use of neuroimaging. Nevertheless, as these cysts enlarge, they may compress surrounding structures and cause neurological symptoms. Patients may present with vague, nonspecific symptoms such as headache, nausea, vomiting, and vertigo. Cranial nerve palsies, including sensorineural hearing loss and facial weakness, although rare, have also been reported in association with posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…Arachnoid cysts of the posterior fossa are commonly diagnosed at prenatal imaging and information given to the parents has to be reassuring: the great majority of arachnoid cysts remains stable and does not require surgical treatment [37]. If the cyst interferes with the CSF circulation, due to its location, and if the patient is symptomatic, surgery is required: when possible, endoscopic fenestration is performed rather than extra- or intracranial shunting [38,39] (fig. 8).…”
Section: Fluid-filled Space-occupying Lesions Of the Posterior Fossa mentioning
confidence: 99%
“…Arachnoid cysts of the posterior fossa are commonly diagnosed at prenatal imaging and information given to the parents has to be reassuring: the great majority of arachnoid cysts remains stable and does not require surgical treatment [37]. If the cyst interferes with the CSF circulation, due to its location, and if the patient is symptomatic, surgery is required: when possible, endoscopic fenestration is performed rather than extra- or intracranial shunting [38,39] (fig. 8).…”
Section: Fluid-filled Space-occupying Lesions Of the Posterior Fossa mentioning
confidence: 99%
“…Recovery of hearing loss secondary to posterior fossa arachnoid cyst surgery in a pediatric patient has been reported [11] . It was reported that even the fenestration of the arachnoid cyst lead to recovery from sensorineural hearing loss in an adult patient [1,12] . According to another case report, cyst decompression could stop progression of hearing loss and render tinnitus more tolerable [13] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the recovery of hearing loss is also possible in some patients who undergo posterior fossa surgery. Arachnoid cyst drainage is one of the interventions, which may result in the recovery of the sensorineural hearing loss [1] . One of the rarely reported reasons might be arachnoid adhesions or arachnoiditis.…”
Section: Introductionmentioning
confidence: 99%
“…Case reports indicate that arachnoid cyst may affect neurological function in the posterior fossa, causing symptoms such as vertigo/dizziness , reversible sensorineural hearing loss or facial palsy . Most likely, these symptoms are caused by direct pressure from the cyst on the cranial nerves or the stretching of them.…”
Section: Introductionmentioning
confidence: 99%